Мировые тенденции проявления оползней - Андреев, Владимир Сергеевич (Global Science Center LP, Czech Republic, 2018)
RUS: В статье выполнен анализ имеющихся в технической литературе данных относительно проявления оползней в различных условиях и странах мира и на этой основе выявлены общие тенденции, присущие данному явлению. Приведенные результаты могут быть использованы для раннего оповещения населения о возможном сходе оползня, совершенствования методов эвакуации населения из оползнеопасных зон, совершенствования противооползневых мероприятий и сооружений и улучшения методов расчета и прогноза устойчивости оползней.

UKR: В статті виконано аналіз наявних в технічній літературі даних щодо прояву зсувів в різних умовах і країнах світу і на цій основі виявлені загальні тенденції, властиві даному явищу. Наведені результати можуть бути використані для раннього оповіщення населення про можливе сходження зсуву, вдосконалення методів евакуації населення з зсувонебезпечних зон, вдосконалення протизсувних заходів і споруд та поліпшення методів розрахунку і прогнозу стійкості зсувів.

ENG: The article analyzes the data available in the technical literature regarding the manifestation of landslides in various conditions and countries of the world and on this basis the general tendencies inherent in this phenomenon are revealed. The resulted results can be used for the early notification of the population about possible descent of a landslide, perfection of methods of evacuation of the population from landslide zones, improvement of anti-landslide actions and constructions and improvement of methods of calculation and forecast of stability of landslips.
Світові тенденції прояву зсувів
World Tendencies of Manifestation of Landslides
В. Андреев: ORCID 0000-0002-0862-2790
Keywords: коэффициент устойчивости; откос (склон); объем перемещенного грунта; человеческие жертвы; аппроксимация; метод наименьших квадратов; оползень; коефіцієнт стійкості; укіс (схил); обсяг переміщеного грунту; людські жертви; апроксимація; метод найменших квадратів; зсув; coefficient of stability; slope; volume of displaced soil; human victims; approximation; least squares method; landslide; КККГ